HOW A MONSTER BECAME A PRINCESS: CURRICULUM DEVELOPMENT - Bothma, Y (South African Journal of Higher Education, 2016)
The nurse educators in a small sub-Saharan African country decided to change their content-driven hospital-based nursing curriculum to a competency-based curriculum with a primary healthcare focus. The high burden of disease and the inability of the country to meet the Millennium Development Goals formed the basis of the decision. The author uses a case study to explain the process used to develop a competency-based curriculum with the aim to reduce curriculum drift. The role players were the nurse educators, Ministry of Health and Welfare, Nurse Education Partnership Initiative, Nurse Capacity Building Programme (ICAP), and Lesotho Nursing Council. A selected task team explained the characteristics of a competency based curriculum, facilitated the process to reach consensus on the key competences, and applied four educational principles in the process to develop the curricula. Consensus on the core competencies were reached by using the nominal group technique. Benchmarking of these competencies was done against international standards.